Perceptions on differences of customer services between public universities (UAs) and private higher education institutions (IPTSs) in Klang Valley, Malaysia - Abdul, Mohani; Abd Rahman, Azmawani; Bularafa, Bukar Ali; Teh, Kwai Wah; Rahman, Mohammad Mizanur (Penerbit Akademia Baru, 2016)
The development of globalized knowledge economy profoundly impacted on the role and value of higher education. Thus, this study seeks to assess the perception of differences of customer services between public universities (UAs) and private higher education institutions (IPTSs) in Malaysia in three main areas: employee's attitude, facilities and evaluation. A quantitative method was adopted for the study with 400 respondents including students and lecturers from the UAs and IPTSs, using questionnaire consisting of 5 points Likert Scale. ANOVA and T-test were used in data analysis for the study. The findings of the study showed that there are significant differences between both the students and lecturers on physical facilities whereby the UAs provide good facilities and technology compared to the IPTSs. Whilst there are significant differences between the students' and lecturers' perceptions of customer services provided by their institutions in all elements of customer service under study for both the UAs and IPTSs. In meeting the competitive demand from their customers, the higher institutions need to assess their customer service and consider some complaints put forward by their customers in upgrading its service performance.